Desenvolvimento de supercapacitores de alto desempenho baseados em eletrodos nanoestruturados e eletrólitos de líquidos iônicos - Joao Paulo Campos Trigueiro (2014)
In this work a fundamental study of different materials (graphene, carbon nanotubes, ionic liquids and poly(ionic liquid)) was performed in order to direct application in the preparation of double layer electrochemical capacitors (supercapacitors). Thermal, morphological and electrical properties of these materials were studied seeking to establish structure-property correlations. Some studies with ionic liquids exhibited good thermal and electrochemical stability, and adequate conductivity for its use as electrolyte in supercapacitors. The reduced graphene oxide nanosheets, either pure (RGO) or modified with poly (ionic liquid), were suitable for use as electrode materials. Supercapacitors in the stacking configuration were constructed from these materials and capacitances up to 71.5 F/g at 25 °C were obtained. The use of poly (ionic liquid) as component material of the supercapacitors electrodes proved to be a promising strategy for achieving devices with high efficiency capacitive. Reduced graphene oxide nanosheets and multi-walled carbon nanotubes were used in the preparation of supercapacitors with in plane configuration. Using this structure it was possible to exploit the maximization in the surface area of the carbon nanomaterials for the development of miniaturized devices with ultrathin characteristics. The combination of RGO and carbon nanotubes proved to be suitable, since those devices with capacitances up to 153.7 F/g at 25 °C were obtained. The devices in both configuration (stacking and in plane) presented good values of energy density and power, long electrochemical stability, compact format and possibility of preparation in flexible shape.